La formation des enseignant·e·s en prise avec les réformes : un rapport au travail (dés)ajusté pour les formateur·trice·s ? - Thérèse Perez-Roux; Christine Françoise; Frédéric Torterat (Éducation et Socialisation)
In France, the latest reform of pre-service teacher training (2019), effective at the beginning of the 2021 academic year, has renewed tensions between the respective approaches to professionalization, academicization and certification. The purpose of this article is to explore the reconfiguration of working and training conditions, and to consider the extent to which the deregulation of institutional requirements has impacted the professional skills of teacher trainers. A questionnaire survey was carried out in spring 2022 among the trainers throughout France (n=725) working in high schools for novice teachers. The results of uni- and bivariate analyses highlight a (dis)adjusted relationship to work and a heightened conflict between theory and practice, between trainers’ beliefs or values and institutional logic. Depending on the trainer’s employment status, the outcomes of the study reveal diverse strategies for (re)giving meaning to action.